2017 ICT Backbone Sector : Private Participation in Infrastructure - World Bank Group (World Bank, Washington, DC, 2018)
Starting in 2017, PPI investment has been reported for ICT-backbone infrastructure (such as fiber-optic cables (land-based/submarine cables), mobile towers, base stations and other hard assets) with an active government component, whereby the government is involved by way of being a contracting authority (i.e., a party to a concession agreement) or the full or part-owner of the assets. Information was also back-filled for the previous 10 years based on the new methodology, therefore this note covers a 10-year period. Tracking private investment in this sector will be increasingly important due to the critical role that ICT plays in development. With some seven billion mobile connections and 60-percent coverage of 3G networks worldwide, the ICT sector is critical for disruptive innovation and for leapfrogging development and enhancing the impact of the fourth Industrial Revolution. In 2017, private investment in ICT amounted to USD 3.0 billion across six projects (including one cross-border project). This marked a significant increase over the investment level of USD 462 million in 2016, as well as the previous 10-year average (2007-2016) of USD 1.3 billion. The 3.2-percent share of ICT in global PPI investment in 2017 marked the second highest share of the last 10 years, after the four-percent share in 2008. However, the ICT sector only accounted for an average of 1.3 percent of global PPI investment over the last 10 years. Overall, there were 37 ICT-backbone projects recorded since 2008, totaling USD 14.1 billion. Of six projects in 2017, two fell into the category of mobile-network infrastructure development. The remaining projects were submarine/land fiber-optic cable-installation projects. The two network development projects, namely the USD 1.5 billion 4G-network-development project in Myanmar and the USD 946 million national-mobile-network development project in Mexico, contributed more than 80 percent of the total ICT investment. The average project size in 2017 (USD 500 million) was almost five times higher than in 2016, because all the projects in 2016 were cable-installation projects, which are typically smaller than network-development projects. However, the average project size in the previous ten-year period was USD 381 million.